2017
DOI: 10.3390/molecules23010058
|View full text |Cite
|
Sign up to set email alerts
|

Flaccidoxide-13-Acetate Extracted from the Soft Coral Cladiella kashmani Reduces Human Bladder Cancer Cell Migration and Invasion through Reducing Activation of the FAK/PI3K/AKT/mTOR Signaling Pathway

Abstract: Metastasis of cancer is the cause of the majority of cancer deaths. Active compound flaccidoxide-13-acetate, isolated from the soft coral Cladiella kashmani, has been found to exhibit anti-tumor activity. In this study, Boyden chamber analysis, Western blotting and gelatin zymography assays indicated that flaccidoxide-13-acetate exerted inhibitory effects on the migration and invasion of RT4 and T24 human bladder cancer cells. The results demonstrated that flaccidoxide-13-acetate, in a concentration-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Akt activation has been correlated with the poor prognostic factor with local recurrence and five-year survival rate for OSCC [ 22 ]. Neoh et al reported that flaccidoxide-13-acetate from the soft coral reduces the cell migration of bladder cancer cells through the down-related Akt/mTOR pathway [ 42 ]. Our results demonstrate that IQ downregulated the phosphorylation of Akt and p38 in OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Akt activation has been correlated with the poor prognostic factor with local recurrence and five-year survival rate for OSCC [ 22 ]. Neoh et al reported that flaccidoxide-13-acetate from the soft coral reduces the cell migration of bladder cancer cells through the down-related Akt/mTOR pathway [ 42 ]. Our results demonstrate that IQ downregulated the phosphorylation of Akt and p38 in OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion kinases (FAK) can be involved in carcinogenic signaling in the invasion and migration of bladder cancer cells ( Kong, Chen & Sima, 2017 ). Neoh et al (2017) reported that inhibition of the expression of MMP-2 and MMP-9 regulated by the FAK/PI3K/AKT/mTOR pathway can inhibit bladder cancer cell migration and invasion. The phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) signaling pathway plays an important role in the occurrence and development of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K pathway is often activated by the silence or genetic loss of phosphatase and tensin homolog and/or the overexpression of protein kinase B [22,23]. The PI3K pathway plays a vital role in carcinogenesis, drug resistance, and programmed cell death of melanoma cells [24][25][26][27][28][29]. Therefore, this pathway is a promising target for melanoma therapy.…”
Section: Introductionmentioning
confidence: 99%